2016
DOI: 10.1016/j.ijid.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Virus susceptibility and clinical effectiveness of anti-influenza drugs during the 2010–2011 influenza season in Russia

Abstract: This study provided experimental and clinical evidence of the efficacy of oseltamivir and umifenovir against influenza viruses, representatives of which have continued to circulate in post-pandemic seasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
44
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 21 publications
(33 reference statements)
9
44
0
3
Order By: Relevance
“…These variants possessed a single amino acid substitution in HA2 subunit (K51N, Q42H, Q27N, or K117R), which lead to reduced ability of umifenovir to stabilize the acid‐induced HA conformational changes. The sequence analysis of 108 clinical isolates obtained during 2010 to 2011 influenza season in Russia did not identify substitutions in the HA2 subunit, that can cause umifenovir resistance among influenza A viruses . This finding supports an earlier report on the absence of naturally occurring variants with low susceptibility to umifenovir among human influenza A and B viruses isolated during 2002 to 2005.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…These variants possessed a single amino acid substitution in HA2 subunit (K51N, Q42H, Q27N, or K117R), which lead to reduced ability of umifenovir to stabilize the acid‐induced HA conformational changes. The sequence analysis of 108 clinical isolates obtained during 2010 to 2011 influenza season in Russia did not identify substitutions in the HA2 subunit, that can cause umifenovir resistance among influenza A viruses . This finding supports an earlier report on the absence of naturally occurring variants with low susceptibility to umifenovir among human influenza A and B viruses isolated during 2002 to 2005.…”
Section: Introductionsupporting
confidence: 82%
“…Co‐crystal structure of umifenovir with the influenza virus HA glycoprotein indicates that umifenovir binds in a hydrophobic cavity at the interface of the HA protomers in the upper region of the stem . Umifenovir inhibits the replication of a wide range of influenza A, B, and C viruses, including highly pathogenic avian A(H5N1) viruses with 50% effective concentration (EC 50 ) ranging from 7.2 to 23.0 µM . It also maintains antiviral activity against oseltamivir‐ and rimantadine‐resistant influenza viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro and in vivo studies have shown that Arbidol has broad-spectrum activity against influenza viruses (16)(17)(18)21). Comparison of the Arbidol-binding site in group 2 HAs against the corresponding region in group 1 HA [H1N1 A/Puerto Rico/8/1934 (H1/PR8; PDB ID code 1RU7)] reveals important structural differences between the two groups ( Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Arbidol (umifenovir) is a broad-spectrum antiviral against a number of enveloped and nonenveloped viruses such as influenza, respiratory syncytial (RSV), adenovirus, Coxsackie B5, parainfluenza, Ebola (EBOV), and hepatitis B and C (14)(15)(16)(17)(18)(19)(20). Arbidol demonstrates broad activity against diverse strains and subtypes of influenza A and B viruses and is effective in mice infected with A/California/07/2009 (H1N1), A/Puerto Rico/8/1934 Significance Influenza virus is an important human pathogen.…”
mentioning
confidence: 99%
See 1 more Smart Citation